Unveiling interfacial dead layer in wurtzite ferroelectrics - Jinlin Wang; Yun-Qin Li; Rui Wang; Qi Liu; Haotian Ye; Ping Wang; Xifan Xu; Huaiyuan Yang; Fang Liu; Bowen Sheng; Liuyun Yang; Xiaoyang Yin; et al. (Nature Communications)
Abstract Wurtzite ferroelectrics hold immense promise to revolutionize modern micro- and nano-electronics due to their compatibility with semiconductor technologies. However, the presence of interfacial dead layers with irreversible polarization limits their development and applications, and the formation mechanisms of dead layers remain unclear. Here, we demonstrate that dead layer formation in ScAlN, a representative wurtzite ferroelectric, originates from a high density of nitrogen vacancies in combination with interfacial strain. Atomic-scale investigations using scanning transmission electron microscopy (STEM) and electron energy loss spectroscopy (EELS), supported by first-principles calculations, reveal that compressive strain near the ScAlN/GaN interface reduces the formation energy of nitrogen vacancies, promoting their generation. These vacancies degrade dielectric properties and raise the ferroelectric switching barrier, the latter further exacerbated by compressive strain. These combined effects suppress polarization reversibility near the interface. This work elucidates the microscopic origin of interfacial dead layers and highlights the significance of defect and strain engineering in wurtzite ferroelectrics, which are essential to advancing their integration and scalability in next-generation electronic devices.